On the Political Genealogy of Trump after Foucault - Bruce M. Knauft (Genealogy, 2018)
How would Foucault have viewed Trump as President, and Trumpism in the US more generally? More realistically, how can we discern and insightfully apply genealogical insights after Foucault to better comprehend and act in relation to our current political situation in the US? Questions of factuality across a base register of asserted falsehoods are now prominent in American politics in ways that put assertions of scholarly objectivity and interpretation in yet deeper question than previously. The extent, range, and vitriol of alt-Right assertions and their viral growth in American media provoke progressivist resistance and anxiety, but how can this opposition be most productively channeled? This paper examines a range of critical perspectives, timeframes, and topical optics with respect to Trump and Trumpism, including nationalist, racist, sexist, class-based, and oligarchical dimensions. These are considered in relation to media and the incitement of polarized subjectivity and dividing practices, and also in relation to Marxist political economy, neoliberalism/neoimperialism, and postcolonialism. I then address the limit points of Foucault, including with respect to engaged political activism and social protest movements, and I consider the relevance of these for the diverse optics that political genealogy as a form of analysis might pursue. Notwithstanding and indeed because of the present impetus to take organized political action, a Foucauldian perspective is useful in foregrounding the broader late modern formations of knowledge, power, and subjectivity within which both Rightist and Leftist political sensibilities in the US are presently cast. At larger issue are the values inscribed through contemporary late modernity that inform both sides of present divisive polarities—and which make the prognosis of tipping points or future political outcomes particularly difficult. As such, productive strategies of activist opposition are likely to vary under alternative conditions and opportunities—including in relation to the particular skills, history, and predilection of activists themselves. If the age of reason threatens to be over, the question of how and in what ways critical intellectualism can connect with productive action emerges afresh for each of us in a higher and more personal key.